2006
DOI: 10.1007/s00425-006-0302-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional roles of the pepper pathogen-induced bZIP transcription factor, CAbZIP1, in enhanced resistance to pathogen infection and environmental stresses

Abstract: Transcription factors often belong to multigene families and their individual contribution in a particular regulatory network remains difficult to assess. We identify and functionally characterize the pepper bZIP transcription factor CAbZIP1 gene isolated from pepper leaves infected with Xanthomonas campestris pv. vesicatoria. Transient expression analysis of the CAbZIP1-GFP fusion protein in Arabidopsis protoplasts revealed that the CAbZIP1 protein is localized in the nucleus. The N-terminal region of CAbZIP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(99 citation statements)
references
References 83 publications
2
96
0
1
Order By: Relevance
“…Based on these results, we propose that all genes involved in ROS signaling are unaffected by multiple stresses. The transcripts of CAbZIP1 are induced by drought and salt stress, which indicates that CAbZIP1 might also be involved in tolerance to environmental stresses (22). The tomato bZIP protein might play an important role in mediating transcriptional activation during wounding responses (13).…”
Section: Sequence Analysis Of Tomato Lebzip2mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these results, we propose that all genes involved in ROS signaling are unaffected by multiple stresses. The transcripts of CAbZIP1 are induced by drought and salt stress, which indicates that CAbZIP1 might also be involved in tolerance to environmental stresses (22). The tomato bZIP protein might play an important role in mediating transcriptional activation during wounding responses (13).…”
Section: Sequence Analysis Of Tomato Lebzip2mentioning
confidence: 99%
“…The tomato bZIP protein might play an important role in mediating transcriptional activation during wounding responses (13). In one study, strong CAbZIP1 gene expression occurred at the early stage of infection in the incompatible interactions (22). Salicylic acid, ethylene and jasmonic acid are involved in disease resistance in plants (23,24).…”
Section: Sequence Analysis Of Tomato Lebzip2mentioning
confidence: 99%
“…To date, numerous genes responsive to drought stress have been isolated from various plant species and their roles in the drought responses have been well studied (Urano et al 2010). Among these genes, the transcription factors (TFs) act as regulators of stress responses by interacting with cis-elements in the promoter region of downstream stress-related genes (Lee et al 2006). Many TFs, such as AP2/EREBP, bZIP, NAC, MYB, MYC, Cys2, His2 zinc-finger and WRKY (Umezawa et al 2006), were known to play pivotal roles in controlling the expression of specific stress-related genes and have been overexpressed in homologous and heterologous systems aiming to enhance stress tolerance (Hadiarto and Tran 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The cDNA consists of 1,255 bp and predicts a 900-bp open reading frame encoding a 33.6-kDa protein of 299 amino acids, which was termed NtbZIP60. Database analysis revealed that, in addition to AtbZIP60, there are several counterpart proteins of NtbZIP60 in pepper (CAbZIP1, accession number AY775332, Lee et al 2006), tomato, soybean, rice and maize. NtbZIP60 shows 75, 36 and 30% identity to CAbZIP1, AtbZIP60 and a gene product of the rice homolog, respectively.…”
Section: Resultsmentioning
confidence: 99%